Use of Posttranscription Gene Silencing in Squash to Induce Resistance against the Egyptian Isolate of the Squash Leaf Curl Virus. (13th March 2016) - Taha, Omnia; Farouk, Inas; Abdallah, Abdelhadi; Abdallah, Naglaa A.
Abstract : Squash leaf curl virus (SqLCV) is a bipartite begomovirus affecting squash plants. It is transmitted by whitefly Bemisia tabaci biotype B causing severe leaf curling, vein banding, and molting ending by stunting. In this study full-length genomic clone of SqLCV Egyptian isolated and posttranscriptional gene silencing (PTGS) has been induced to develop virus resistance. The Noubaria SqLCV has more than 95% homology with Jordon, Israel, Lebanon, Palestine, and Cairo isolates. Two genes fragment from SqLCV introduced in sense and antisense orientations using pFGC5049 vector to be expressed as hairpin RNA. The first fragment was 348 bp from replication associated protein gene ( Rep ). The second fragment was 879 bp representing the full sequence of the movement protein gene ( BC1 ). Using real-time PCR, a silencing record of 97% has been recorded to Rep/TrAP construct; as a result it has prevented the appearance of viral symptoms in most tested plants up to two months after infection, while construct containing the BC1 gene scored a reduction in the accumulation of viral genome expression as appearing in real-time PCR results 4.6-fold giving a silencing of 79%, which had a positive effect on symptoms development in most tested plants.